2004
DOI: 10.4049/jimmunol.173.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated FcεRI Signaling and Altered Fyn and SHIP Activities in Lyn-Deficient Mast Cells

Abstract: Studies in B cells from Lyn-deficient mice have identified Lyn as both a kinetic accelerator and negative regulator of signaling through the BCR. The signaling properties of bone marrow-derived mast cells from Lyn−/− mice (Lyn−/− BMMCs) have also been explored, but their signaling phenotype remains controversial. We confirm that Lyn−/− BMMCs release more β-hexosaminidase than wild-type BMMCs following FcεRI cross-linking and show that multiple mast cell responses to FcεRI cross-linking (the phosphorylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
147
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(164 citation statements)
references
References 71 publications
13
147
3
1
Order By: Relevance
“…Intriguingly, Lyn-deficient B cells are also hyperresponsive to anti-IgMinduced proliferation and demonstrate enhanced activation of mitogen-activated protein kinase and sustained calcium mobilization [21][22][23]26]. Hernandez-Hansen et al [32] have shown that dysregulated signaling in Lyn-deficient mast cells is due in part to enhanced Fyn activation, and a recent study by Hong et al [33] suggested that the Src kinase Hck regulates mast cell activation by suppressing activation of Lyn. These results suggest that regulation of SFKs in HSC/Ps is likely to be complex and may depend on the stimulus and development stage of the cells under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, Lyn-deficient B cells are also hyperresponsive to anti-IgMinduced proliferation and demonstrate enhanced activation of mitogen-activated protein kinase and sustained calcium mobilization [21][22][23]26]. Hernandez-Hansen et al [32] have shown that dysregulated signaling in Lyn-deficient mast cells is due in part to enhanced Fyn activation, and a recent study by Hong et al [33] suggested that the Src kinase Hck regulates mast cell activation by suppressing activation of Lyn. These results suggest that regulation of SFKs in HSC/Ps is likely to be complex and may depend on the stimulus and development stage of the cells under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Ca 2ϩ response in Lyndeficient mast cells was impaired at early transient stage of the response and was almost intact at the later prolonged phase (48,50,51) with one exception in which Lyn deficiency caused a marked decrease in overall Ca 2ϩ response (49). It should be noted that Stim1-deficient mast cells showed severely impaired sustained Ca 2ϩ increase and degranulation (64).…”
Section: Discussionmentioning
confidence: 99%
“…IgE-induced ITAM phosphorylation, PLC-γ activation and Ca 2+ mobilization were reduced but persisted longer [28]; PI(3,4,5)P3 levels, and Fyn activity were however markedly enhanced in Lyn -/-mast cells. Increased PI(3,4,5)P3 levels were accounted for by an impaired activity of SHIP1 [28] and Fyn hyperactivity by an abrogation of Lyndependent phosphorylation of Csk-Binding Protein (Cbp) which mediates the recruitment of Csk. Csk phosphorylates regulatory tyrosines in Fyn and thereby inhibits its catalytic activity.…”
Section: Signaling Molecules In Negative Regulationmentioning
confidence: 90%